Improving energy efficiency of the traction system of mainline locomotives - Sych, Oleg (National Technical University "Kharkiv Polytechnic Institute", 2024)
Various methods for improving the traction and energy characteristics of locomotives are discussed. To reduce fuel and energy consumption, implementation of energy accumulation in the onboard energy storage during electrodynamic braking is necessary. In the case of operating locomotives on partially electrified lines, it is beneficial to create locomotives with the ability to be powered from both the contact network and a diesel generator.
Keywords: traction systems; mainline locomotives; asynchronous electric motors; synchronous-reactive electric motors; energy efficiency